Organización Contable de la Empresa “Queso Saraguro” del Cantón Saraguro. Periodo Octubre - Diciembre 2022. - Guamán Paqui, Diana Maribel (2023)
The present Curricular Integration Project titled “Accounting Organizational Structure of the 'Queso Saraguro' Company' in the Saraguro Canton, period October - December 2022”, was developed with the objective of introducing advanced accounting tools. These tools are intended to empower the owner with a comprehensive understanding of the company's true financial standing and make informed decisions to enhance business performance. In order to achieve the objectives outlined in the present Curricular Integration Project, the process initiated with an examination of the corporate landscape. Subsequently, a meticulously structured and systematically coded Chart of Accounts was developed in alignment with the specific economic activities. This chart was conceived as an essential instrument for the implementation of sound accounting practices. Following this, the process proceeded to the assessment of the Initial Inventory. This assessment involved a comprehensive review of source documentation to physically verify and quantify the assets, monetary values, legal rights, and financial obligations with which the company begins its operations. The results revealed total assets of $59,612.70, liabilities amounting to $4,311.14, and equity totaling $55,301.56. These findings led to the preparation of the Initial Statement of Financial Position. Finally, the comprehensive and requisite documentation necessary for the implementation of the accounting process was methodically gathered and organized. This included auxiliary records covering purchases, sales, production orders, purchase requisitions, purchase orders, material requisition notes, inventory records (kárdex), depreciation schedules, timekeeping records, employee timecards, payroll registers, payrolls, and timecards. Subsequently, a memorandum of operations was crafted to facilitate the systematic and chronological recording of economic transactions within the General Journal. The data was consolidated into the general ledgers to prepare the Trial Balance and Worksheet, incorporating adjustments made during the accounting period. Furthermore, it serves as the creation of several financial statements, including the Cost of Goods Sold Statement, Statement of Financial Position, Income Statement, and Cash Flow Statement. Consequently, the company reported total assets of $65,961.23, liabilities of $9,601.99, equity of $56,359.24, revenues of $22,560.58, expenses of $1,267.55, and a net profit of $1,057.68." In the course of conducting this study, it became apparent that the economic activity pursued is indeed lucrative. This conclusion is drawn from calculating the unit cost of the finished product.